Safeguards Assessments : 2012 Update. (Policy Papers; Policy Paper ;, 2012)
The safeguards policy was introduced in 2000 to reduce the risks of misuse of Fund resources and misreporting of program monetary data to the Fund. It supports the Fund's approach to prudent lending and complements other safeguards such as program design, conditionality, and access limits, to name a few. Some 242 assessments of 92 central banks have been completed since 2000. Assessments are followed by a period of monitoring for as long as Fund credit is outstanding.